2006
DOI: 10.1021/ic060984e
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Only Hydrogenase Mimics. Thermodynamic Aspects of the Use of Electrochemistry to Evaluate Catalytic Efficiency for Hydrogen Generation

Abstract: Voltammetry is widely used for the evaluation of iron-only hydrogenase mimics and other potential catalysts for hydrogen generation using various dipolar aprotic solvents. Effective catalysts show enhanced current in the presence of a proton donor at the potential where the catalyst is reduced. To facilitate the comparison of catalytic efficiencies, this paper provides a simple means of calculating the standard potential for reduction of the acid, HA, according to the half reaction 2HA + 2e- <==> H2 + 2A-. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
402
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 436 publications
(422 citation statements)
references
References 17 publications
16
402
0
4
Order By: Relevance
“…These results indicated that acetic acid was not strong enough to protonate the Ni center of [ Ni‐P ] − , and catalytic H 2 evolution was initiated upon 2 e − reduction to [ Ni‐P ] 2− . Importantly, upon the addition of TFA (p K a =12.7 in acetonitrile),46 the first reduction wave exhibited pronounced catalytic activity (Figure 2 B). At low TFA concentrations, the catalytic current i c increased linearly with the acid concentration (see Figure S6), but reached an acid‐independent region with more than 108 m m of TFA (see Figure S4).…”
mentioning
confidence: 99%
“…These results indicated that acetic acid was not strong enough to protonate the Ni center of [ Ni‐P ] − , and catalytic H 2 evolution was initiated upon 2 e − reduction to [ Ni‐P ] 2− . Importantly, upon the addition of TFA (p K a =12.7 in acetonitrile),46 the first reduction wave exhibited pronounced catalytic activity (Figure 2 B). At low TFA concentrations, the catalytic current i c increased linearly with the acid concentration (see Figure S6), but reached an acid‐independent region with more than 108 m m of TFA (see Figure S4).…”
mentioning
confidence: 99%
“…With excess lutH + ,the current density increased to j c /j p = 10; this result suggested that ac atalytic event had occurred ( Figure 2a). [15] Controlled potential electrolysis (CPE) experiments performed with 0.3 mm 1 and 20 equivalents of acid at À1.16 Vo ver 1.5 h ( Table 1a nd Figure S1 in the Supporting Information) indicated that H 2 was produced with 70 or 85 %F aradaic efficiency( FE) using lutH + or 4-dimethylaminopyridinium (DMAPH + ), respectively.Q uantification of H 2 was performed by using gas chromatography with at hermal conductivity detector (GC-TCD) on samples taken from the headspace of the CPE experiment. To [12] Ar = diisopropylphenyl.…”
Section: Akeyareaofresearchintofuel-producingelectrocatalystsismentioning
confidence: 99%
“…Our previous reports on the [c] Thermodynamic potentialf or H + reduction calculated from pK a in THF (see the SupportingInformation for details). [15][16][17] [d] With respect to E cat/2 for reduction of the catalyst. [18] [e] With respect to applied potential of the CPE experiment: À1.16 Vfor 1 and À1.22 Vf or 2. .…”
Section: Akeyareaofresearchintofuel-producingelectrocatalystsismentioning
confidence: 99%
“…Als letzte Klasse wären noch Organometallverbindungen mit Cyclopentadienyl- (30)(31)(32)(33) [63,65,66] oder Diphosphanliganden (34) [67,68] [72] Somit erhält man ein Maß für den Energieaufwand, der betrieben werden muss, damit die Reaktion mit einer signifikanten Geschwindigkeit ablaufen kann. [72][73][74] Der zweite charakteristische Parameter eines Katalysators ist seine Umsatzfrequenz ("turnover frequency", TOF). Weil der Strom an einer Elektrode mit der Zahl an Elektronen korreliert, die pro Sekunde mit den redoxaktiven Verbindungen in Lösung -in diesem Fall mit dem Katalysatorausgetauscht werden, besteht eine direkte Beziehung zwischen der Umsatzfrequenz und dem cyclovoltammetrisch gemessenen Katalysestrom.…”
Section: Cobaltkatalysatoren Für Die Wasserstofferzeugungunclassified